(untitled) (TEL Tempo, Espaço e Linguagem, 2019)
Abstract: This paper aimed at analysing the discourses related to motherhood when it comes to the theme of abortion. The analyses were based on the theoretical-methodological studies of Pecheutian Discourse Analysis, from which we took the notion of discursive formation. It was concluded that arguments against abortion are composed of several discursive formation, besides a interdiscourse on motherhood inherent to the feminine and place of unconditional love. Keywords: Motherhood. Discourse Analysis. Abortion. Media.